The research and realization of wireless energy consumption detector based on the internet of things - Fu, W.; Shui, M.; Chen, Y.; Chen, L. (Journal of Digital Information Management, 2013)
Intelligent power consumption detection device is an important part in Smart Home system, which can intelligent identification , positioning , tracking, monitoring and management the household electrical parameters, enabling users to keep abreast of household electricity consumption. This paper is mainly about the design of a Wireless Energy Consumption Detector (WECD) based on the Internet of Things, combine with the IEEE802.15.4E wireless protocol. The whole system includes hardware and software parts, the choice of MCU chip, RF chip and power measurement chip for WECD, the design of each module circuit based on the chip working principle, the paper also make a key analysis of device driver module, wireless data forwarding module and wireless data showing module of indoor terminal. After a series of rigorous testing, the result indicates a high reliability and accuracy of the WECD.
Keywords: IEEE802.15.4E; Smart home; Wireless energy consumption detector

Reasoning on context satisfiability for service recommendation in mobilenetwork - Kuang, L.; Chen, L.; Xia, Y. (Journal of Digital Information Management, 2011)
The Ubiquitous Computing envisions a world of communicating mobile devices. As mobile devices usually have limited resources, it brings up the challenge to search and invoke services at any time and any place in an accurate, efficient and adaptive way. In this paper, we propose to filter services by matchmaking the precondition of service invocation and the context information of service consumer, in order to increase the accuracy and adaptivity of service discovery and recommendation in mobile environment. We construct context ontology to describe the environment when a service consumer submits service request first. And then, we propose to formalize the precondition of a successful service invocation based on a lightweight DL theory. Finally, reasoning on context satisfiability can be used for service recommendation. A case study shows our approach works well.
Keywords: Context Satisfiability; Precondition Formalization; Service Reasoning; Service Recommendation